2018
DOI: 10.1021/acsami.8b03023
|View full text |Cite
|
Sign up to set email alerts
|

Porous Silsesquioxane–Imine Frameworks as Highly Efficient Adsorbents for Cooperative Iodine Capture

Abstract: The efficient capture and storage of radioactive iodine (I or I), which can be formed during nuclear energy generation or nuclear waste storage, is of paramount importance. Herein, we present highly efficient aerogels for reversible iodine capture, namely, porous silsesquioxane-imine frameworks (PSIFs), constructed by condensation of octa(3-aminopropyl)silsesquioxane cage compound and selected multitopic aldehydes. The resulting PSIFs are permanently porous (Brunauer-Emmet-Teller surface areas up to 574 m/g), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 73 publications
1
42
0
Order By: Relevance
“…Iodine uptake [88] PAN3 Phenyl and pyrrolyl rings Iodine uptake [89] MelPOP-2 and TatPOP-2 50.5 and 36.5 Phosphorus and nitrogen heteroatoms, and p-π conjugated units Iodine uptake [90] COF-DL229 1762 π-conjugated pore walls Iodine uptake [91] CalPOF Azo groups, macrocyclic π-rich cavities and phenolic units Iodine uptake [92] PHF-1-Ct Positive charge and nitrogen Iodine uptake [93] PSIFs Imine groups and silsesquioxane Iodine uptake [94] HCMP-1, 2, 3, 4 Amine groups Iodine uptake [95] Azo-Trip 510. different mechanisms of separation, we will summarize the novel porous polymers in both adsorption and membrane separation area. As a kind of traditional ion-exchange resins, crosslinked polystyrene-based resins and their carbonized derivatives have found wide applications in material adsorption, extraction, and analysis.…”
Section: Ahcp-1 Sodium Tetraphenylboronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine uptake [88] PAN3 Phenyl and pyrrolyl rings Iodine uptake [89] MelPOP-2 and TatPOP-2 50.5 and 36.5 Phosphorus and nitrogen heteroatoms, and p-π conjugated units Iodine uptake [90] COF-DL229 1762 π-conjugated pore walls Iodine uptake [91] CalPOF Azo groups, macrocyclic π-rich cavities and phenolic units Iodine uptake [92] PHF-1-Ct Positive charge and nitrogen Iodine uptake [93] PSIFs Imine groups and silsesquioxane Iodine uptake [94] HCMP-1, 2, 3, 4 Amine groups Iodine uptake [95] Azo-Trip 510. different mechanisms of separation, we will summarize the novel porous polymers in both adsorption and membrane separation area. As a kind of traditional ion-exchange resins, crosslinked polystyrene-based resins and their carbonized derivatives have found wide applications in material adsorption, extraction, and analysis.…”
Section: Ahcp-1 Sodium Tetraphenylboronsmentioning
confidence: 99%
“…The enhanced adsorption performance can be realized by presetting N heteroatomic units, such as amine, imine, pyrrole, and other N containing rings. [88][89][90][92][93][94][95][96][97][98]100] The π-conjugated structure in aromatic frameworks also increased the adsorption affinity to iodine species. [88,[90][91][92]97,99] Moreover, other heteroatoms (P, S, and B), [87,90,100] phenolic groups, [92] and charged groups [86,93] are also beneficial to elevate the uptake performance.…”
Section: Radionuclide Extractionmentioning
confidence: 99%
“…38 However, to achieve these values, these adsorbents took significantly longer time (12-30 h), leaving our mPTPM-3 as a fast and efficient adsorbent for I2. Previous studies showed that I2 desorption can be readily induced by heating the I2loaded samples at 393-473 K, [39][40][41] providing a facile route to recover the adsorbents.…”
Section: Resultsmentioning
confidence: 99%
“…synthesized an azo‐linked porous organic network that exhibits an excellent guest uptake of 238 wt% in iodine vapor and reversible adsorption of iodine in solution. Janeta et al . present a porous aerogel for reversible idone capture with extremely high affinity with uptake capacity up to 485 wt %.…”
Section: Introductionmentioning
confidence: 99%
“…Dang et al [19] synthesized an azolinked porous organic network that exhibits an excellent guest uptake of 238 wt% in iodine vapor and reversible adsorption of iodine in solution. Janeta et al [20] present a porous aerogel for reversible idone capture with extremely high affinity with uptake capacity up to 485 wt %. In our previous work, we synthesized N-rich porous organic polymers as sorbents for remediation of iodine vapor with a high capacity up to 382 wt %.…”
Section: Introductionmentioning
confidence: 99%